A prospective observational cohort study of the efficacy of tofacitinib plus iguratimod on rheumatoid arthritis with usual interstitial pneumonia - Wang, Shuhua; Li, Yao; Tang, Yanchun; Xie, Weilin; Zhang, Yue; Liu, Qingyan (Frontiers in Immunology, 2023)
Objectives To assess the efficacy of tofacitinib (TOF) plus iguratimod (IGU) in rheumatoid arthritis (RA) with usual interstitial pneumonia (UIP) (RA-UIP). Methods This was an prospective observational cohort, single-center study. Data from 78 RA-UIP patients treated with TOF plus IGU, IGU plus conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) and csDMARDs were analyzed. A clinically relevant response in RA activity assessment, pulmonary function tests (PFTs) and high-resolution computed tomography (HRCT) assessment at baseline and follow-up were compared between the groups to evaluate the efficacy of TOF plus IGU. Results A total of 78 patients were followed up at least 6 months after treatment. There were significant changes in RF, CCP, CRP and ESR during the follow-up within each treatment group, but there was no statistically significant difference between two groups. After 6 months of TOF plus IGU treatment, FVC% (84.7 ± 14.7 vs 90.7 ± 15.4) and HRCT fibrosis score (7.3 ± 3.4 vs 7.0 ± 5.6) showed significant improvement compared to the csDMARD group (P=0.031, P=0.015). The TOF plus IGU-treated patients had a significantly higher regression and lower deterioration than the csDMARD-treated patients (P=0.026, P=0.0026) and had a significantly higher response (regression+stability), with overall response rates of 66.7% (16/24) vs 35.7% (10/28) (P=0.027), respectively. Conclusion Our results indicate that TOF plus IGU can simultaneously relieve RA and RA-UIP, and be better than the csDMARDs with a higher response rate in RA-UIP, which may be a potential choice for "dual treat-to-target".